2012
DOI: 10.1098/rsif.2012.0507
|View full text |Cite
|
Sign up to set email alerts
|

The biological seal of the implant–soft tissue interface evaluated in a tissue-engineered oral mucosal model

Abstract: For dental implants, it is vital that an initial soft tissue seal is achieved as this helps to stabilize and preserve the peri-implant tissues during the restorative stages following placement. The study of the implant -soft tissue interface is usually undertaken in animal models. We have developed an in vitro three-dimensional tissue-engineered oral mucosal model (3D OMM), which lends itself to the study of the implant -soft tissue interface as it has been shown that cells from the three-dimensional OMM attac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
37
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 25 publications
3
37
1
Order By: Relevance
“…Titanium (Ti) has been widely used as abutment material due to its superior corrosion resistance, high strength‐to‐weight ratio, and biocompatibility . Studies have shown evidence of soft tissue attachment to the Ti surfaces, which could form a biological seal around the implant . Various Ti surface modifications to optimize the soft tissue attachment on the Ti abutments have been investigated .…”
Section: Introductionmentioning
confidence: 99%
“…Titanium (Ti) has been widely used as abutment material due to its superior corrosion resistance, high strength‐to‐weight ratio, and biocompatibility . Studies have shown evidence of soft tissue attachment to the Ti surfaces, which could form a biological seal around the implant . Various Ti surface modifications to optimize the soft tissue attachment on the Ti abutments have been investigated .…”
Section: Introductionmentioning
confidence: 99%
“…22,[28][29][30] In recent years, emphasis has shifted from solely focusing on osseointegration to considering the role that the surrounding soft tissue has in preventing bacteria infiltration around the implant, although inflammation of marginal soft tissue after implant placement has always been explored. [31][32][33][34][35][36] Gingival fibroblasts establish a soft tissue seal around the neck of tissue level implant components that inhibits further bacterial penetration to the bone-implant interface. 31 However, the integrity of this soft tissue seal is also vulnerable to bacteria, especially immediately post-surgery.…”
mentioning
confidence: 99%
“…[31][32][33][34][35][36] Gingival fibroblasts establish a soft tissue seal around the neck of tissue level implant components that inhibits further bacterial penetration to the bone-implant interface. 31 However, the integrity of this soft tissue seal is also vulnerable to bacteria, especially immediately post-surgery. 33 A study by Zhao and colleagues and others presented the idea of a "race-for-the-surface" between bacterial cells and mammalian gingival cells as a defining factor in the establishment of this soft tissue seal, and overall soft-tissue health.…”
mentioning
confidence: 99%
“…[10][11][12] Failures can be caused by surgical or patient-related factors like smoking status or existing medical conditions, but bacterial infection plays a large role in implant failures. [16][17][18] Currently, there are surface treatment methods that specifically seek to alter the surface of titanium to decrease the incidences of bacteria-based failures on the implant body. Conversely, late colonizing anaerobic bacteria can penetrate an already osseointegrated implant, inducing an inflammatory response, which can cause resorption of hard and soft tissues, known as peri-implantitis.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 During implantation, bacteria can encapsulate parts of the implant surface with a biofilm, inhibiting osseointegration and causing early implant failure. 5,16,[19][20][21] A particularly popular treatment, anodization, treats titanium as an anode in a potentiostatic or galvanostatic cell, which thickens the materials oxide layer. 9,11,14,15 Recently, the formation of a soft tissue seal around the implant has been examined as a vital factor in preventing the infiltration of bacteria into the bone-implant interface.…”
Section: Introductionmentioning
confidence: 99%